PENGARUH PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT , INTELLECTUAL CAPITAL, CORPORATE SOCIAL RESPONSIBILITY, DAN SUSTAINABILITY REPORT TERHADAP NILAI PERUSAHAAN - Nolita Yeni Siregar; Tiara Amelia Safitri (Jurnal Bisnis Darmajaya, 2019)
The objective of this research was proving empirically the effect of the enterprise risk management disclosure, the intellectual capital disclosure, the corporate social responsibility disclosure, and the sustainability report disclosure on the firm values. The population of this research was the mining companies indexed in Indonesia Stock Exchange in 2013-2017. The sampling technique used in this research was the purposive sampling. A number of samples used in this research were 6 companies. The time of this research was 2013-2017 so that the number of the observed data in this research was 30 data. The data analysis technique used in this research was the multiple linear regression. The analytical tool used in this research was SPSS V.20. The result of this research showed that the corporate social responsibility disclosure and the sustainability report disclosure had a significant effect on the firm value; moreover, the enterprise risk management disclosure and the intellectual capital disclosure did not have a significant effect on the firm value.Keywords — Enterprise Risk Management Disclosure, Intellectual Capital Disclosure, Corporate Social Responsibility Disclosure, Sustainability Report Disclosure, firm Value